Integrating knowledge and action: learnings from an implementation program for food security and food sovereignty with First Nations communities within Canada - Ashleigh Domingo; Jennifer Yessis; Kerry-Ann Charles; Kelly Skinner; Rhona M. Hanning (Implementation Science, 2023)
Abstract Background Collaborative approaches to knowledge translation (KT) are important for advancing community-engaged research. However, there is a need for examples of participatory approaches that have effectively supported public health research, program development, and implementation with First Nations communities. To strengthen KT with communities, we proposed a set of guiding principles for participatory planning and action for local food system change. Principles emerged from a cross-community analysis of Learning Circles: Local Healthy Food to School (LC:LHF2S) a participatory program (2015–2019) for Indigenous food system action. The objective was to identify guiding principles for participatory planning and action from key learnings and successes on scaling-up of the Learning Circles (LC) model vertically in Haida Nation, British Columbia (BC), and horizontally in three distinct community contexts: Gitxsan Nation, Hazelton /Upper Skeena, BC; Ministikwan Lake. The application of these principles is discussed in the context of our ongoing partnership with Williams Treaties First Nations to support community planning to enhance food security and sovereignty. Methods A cross-community thematic analysis was conducted and guided by an implementation science framework, Foster-Fishman and Watson’s (2012) ABLe Change Framework, to identify key learnings and successes from adapting the LC approach. Information gathered from interviews (n = 55) and meeting reports (n = 37) was thematically analyzed to inform the development of guiding principles. Community sense-making of findings informed applicability in a new community context embarking on food systems work. Results Emergent guiding principles for participatory food system planning and action are described within four main areas: (1) create safe and ethical spaces for dialog by establishing trust and commitment from the ground up, (2) understand the context for change through community engagement, (3) foster relationships to strengthen and sustain impact, and (4) reflect and embrace program flexibility to integrate learnings. Conclusions Emergent principles offer guidance to supporting Indigenous community-led research and mobilization of knowledge into action. Principles are intended to support researchers and health system administrators with taking a collaborative approach that fosters relationships and integration of community leadership, knowledge, and action for food system change. Application of principles with implementation frameworks can strengthen KT in Indigenous contexts by incorporating community protocols and perspectives in support of Indigenous self-determined priorities.